Anti-ulcerogenic effect of methanolic extracts from Enicosanthellum pulchrum (King) Heusden against ethanol-induced acute gastric lesion in animal models - Noraziah Binti Nordin; Suzy Munir Salama; Shahram Golbabapour; Maryam Hajrezaie; Pouya Hassandarvish; Behnam Kamalidehghan; Nazia Abdul Majid; Najihah Mohd Hashim; Hanita Omar; Mehran Fadaienasab; Hamed Karimian; Hairin Taha; et al. (Public Library of Science (PLOS), 2024)
A natural source of medicine, Enicosanthellum pulchrum is a tropical plant which belongs to the family Annonaceae. In this study, methanol extract from the leaves and stems of this species was evaluated for its gastroprotective potential against mucosal lesions induced by ethanol in rats. Seven groups of rats were assigned, groups 1 and 2 were given Tween 20 (10% v/v) orally. Group 3 was administered omeprazole 20 mg/kg (10% Tween 20) whilst the remaining groups received the leaf and stem extracts at doses of 150 and 300 mg/kg, respectively. After an additional hour, the rats in groups 2-7 received ethanol (95% v/v; 8 mL/kg) orally while group 1 received Tween 20 (10% v/v) instead. Rats were sacrificed after 1 h and their stomachs subjected to further studies. Macroscopically and histologically, group 2 rats showed extremely severe disruption of the gastric mucosa compared to rats pre-treated with the E. pulchrum extracts based on the ulcer index, where remarkable protection was noticed. Meanwhile, a significant percentage of inhibition was shown with the stem extract at 62% (150 mg/kg) and 65% (300 mg/kg), whilst the percentage with the leaf extract at doses of 150 and 300 mg/kg was 63% and 75%, respectively. An increase in mucus content, nitric oxide, glutathione, prostaglandin E2, superoxide dismutase, protein and catalase, and a decrease in malondialdehyde level compared to group 2 were also obtained. Furthermore, immunohistochemical staining of groups 4-7 exhibited down-regulation of Bax and up-regulation of Hsp70 proteins. The methanol extract from the leaves and the stems showed notable gastroprotective potential against ethanol.